POTENSI INTERAKSI OBAT PADA PASIEN GASTRITIS DI PUSKESMAS RAWAT INAP WAY KANDIS BANDAR LAMPUNG TAHUN 2020 - Lilik Koernia Wahidah; Novita Tri Wahyuni; Cahya Rizky Amaliana (JFL : Jurnal Farmasi Lampung, 2021)
ABSTRACT Gastritis is an inflammatory process in the mucous and sub-mucous layers of the stomach. The use of several drugs simultaneously facilitates the occurrence of drug interactions that are part of the Drug Related Problem (DRPs). This study aims to determine the potential for drug interactions in gastritis patients at the Puskesmas Rawat Inap Way Kandis Bandar Lampung in 2020. The research method carried out is observational research with a descriptive design taken retrospectively. The results of the study based on gender showed that there were 34 male patients (40.5%) and 50 female patients (59.5%). Then, based on the age group of 17-25 years, there were 26 patients (31%), aged 26-35 years as many as 16 patients (19%), aged 36-45 as many as 19 patients (22.6%), aged 46-55 as many as 13 patients (15.5%), aged 56-65 as many as 5 patients (6%), and aged >65 years as many as 5 patients (6%). The most use of gastritis drugs are antacids (92.8%), omeprazole (21.4%), ranitidine (15.1%). Drug interactions based on pharmacokinetic mechanisms were 20 cases (58.8%), and pharmacodynamic mechanisms were 14 cases (41.1%). Severity, 18 cases (52.9%) minor, 14 cases (41.1%) moderate, and 2 cases (5.8%) major. It was concluded that the potential drug interactions that experienced the incidence of drug interactions were 27 samples (32.1%) and 57 samples (67.8%) did not experience drug interactions. Â Keywords : Antacids, DRPs, Drug Interactions, Gastritis, Omeprazole, Ranitidine